Low urine pH is a risk factor for low muscle mass: A new way to predict sarcopenia. Issue 10 (28th August 2021) - Yang, Shih‐Wei; Lin, Yu‐Jen; Cheng, Yung‐Wen; Chen, Yuan‐Yuei; Chen, Wei‐Liang
Abstract : Aims: Sarcopenia, one of the primary diseases of the older adult population, is a condition characterized by loss of skeletal muscle mass, strength and functionality. Due to its considerable economic impact, preventive interventions for sarcopenia play an important role in the older adult population. Urine includes many indicators of physiology and pathophysiology. Urine analysis is used to diagnose many different diseases. The goal of this cohort study was to examine the relationship between urine pH level and skeletal muscle mass. Methods: This community‐based cross‐sectional study was carried out among 9712 Taiwanese individuals (4992 men and 4720 women). We used urine pH as an independent variable and skeletal muscle mass as a dependent variable. Bioelectric impedance analysis was used to measure the percentage of skeletal muscle mass (PSMM). We collected first fasting morning urine samples after overnight fasting, and urine pH was measured with a dipstick. In the by‐sex and by‐obesity analyses, we stratified the sample into two subgroups and a linear regression model was used for covariate adjustment. Results: In the fully adjusted model, all‐subject analysis showed a statistically significant association between urine pH and the PSMM with a β coefficient of 0.820 (95% CI 0.615–1.025; P  < 0.001). Additionally, by‐sex analysis showed that urine pH was related to the PSMM in both sexes, with β coefficients of 0.261 (95% CI 0.006–0.516; P  = 0.045) in men and 0.179 (95% CI 0.029–0.328; P  = 0.019) in women. By‐obesity status analysis showed that urine pH was related to the PSMM in the body mass index <27 group with a β coefficient of 0.284 (95% CI 0.101–0.466; P  = 0.002) after full adjustment. However, for the body mass index ≥27 group, there was no significant relationship between urine pH and the PSMM ( P  > 0.05). Conclusion: The results showed the impacts of urine pH levels on skeletal muscle mass in both sexes and non‐obese populations. Due to its easily accessible and economical characteristics, urine analysis is a convenient way to approach patients with low skeletal muscle mass and predict sarcopenia. Geriatr Gerontol Int 2021; 21: 944–949 .